A web platform for the network analysis of high-throughput data in melanoma and its use to investigate mechanisms of resistance to anti-PD1 immunotherapy - Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Jaitly, Tanushree; Walter, Lisa; Wittmann, Jürgen; Gupta, Shailendra; Khan, Faiz M.; Wolkenhauer, Olaf; Puetzer, Brigitte M.; Jäck, Hans-Martin; Heinzerling, Lucie; et al. (Biochimica et Biophysica Acta - Molecular Basis of Disease, 2018)
Cellular phenotypes are established and controlled by complex and precisely orchestrated molecular networks. In cancer, mutations and dysregulations of multiple molecular factors perturb the regulation of these networks and lead to malignant transformation. High-throughput technologies are a valuable source of information to establish the complex molecular relationships behind the emergence of malignancy, but full exploitation of this massive amount of data requires bioinformatics tools that rely on network-based analyses. In this report we present the Virtual Melanoma Cell, an online tool developed to facilitate the mining and interpretation of high-throughput data on melanoma by biomedical researches. The platform is based on a comprehensive, manually generated and expert-validated regulatory map composed of signaling pathways important in malignant melanoma. The Virtual Melanoma Cell is a tool designed to accept, visualize and analyze user-generated datasets. It is available at: https://www.vcells.net/melanoma. To illustrate the utilization of the web platform and the regulatory map, we have analyzed a large publicly available dataset accounting for anti-PD1 immunotherapy treatment of malignant melanoma patients.
EVALuna2:34379
Keywords: Therapy resistance; Databases; Network genomics; Systems biology; Immunotherapy; Melanoma

Dicer ablation in osteoblasts by Runx2 driven cre-loxP recombination affects bone integrity, but not glucocorticoid-induced suppression of bone formation - Liu, Peng; Baumgart, Mario; Groth, Marco; Wittmann, Jürgen; Jäck, Hans-Martin; Platzer, Matthias; Tuckermann, Jan P.; Baschant, Ulrike (Scientific Reports, 2016)
Glucocorticoid-induced osteoporosis (GIO) is one of the major side effects of long-term glucocorticoid (GC) therapy mediated mainly via the suppression of bone formation and osteoblast differentiation independently of GC receptor (GR) dimerization. Since microRNAs play a critical role in osteoblast differentiation processes, we investigated the role of Dicer dependent microRNAs in the GC-induced suppression of osteoblast differentiation. MicroRNA sequencing of dexamethasone-treated wild-type and GR dimer-deficient mesenchymal stromal cells revealed GC-controlled miRNA expression in a GR dimer-dependent and GR dimer-independent manner. To determine the functional relevance of mature miRNAs in GC-induced osteoblast suppression, mice with an osteoblast-specific deletion of Dicer (Dicer(Runx2Cre)) were exposed to glucocorticoids. In vitro generated Dicer-deficient osteoblasts were treated with dexamethasone and analyzed for proliferation, differentiation and mineralization capacity. In vivo, abrogation of Dicer-dependent miRNA biogenesis in osteoblasts led to growth retardation and impaired bone formation. However, subjecting these mice to GIO showed that bone formation was similar reduced in Dicer(Runx2Cre) mice and littermate control mice upon GC treatment. In line, differentiation of Dicer deficient osteoblasts was suppressed to the same extent as wild type cells by GC treatment. Therefore, Dicer-dependent small RNA biogenesis in osteoblasts plays only a minor role in the pathogenesis of GC-induced inhibition of bone formation.
EVALuna2:13640

Direct uptake of Antagomirs and efficient knockdown of miRNA in primary B and T lymphocytes - Haftmann, Claudia; Riedel, Rene; Porstner, Martina; Wittmann, Jürgen; Chang, Hyun-Dong; Radbruch, Andreas; Mashreghi, Mir-Farzin (Journal of Immunological Methods, 2015)
Depending on their physiological expression level, microRNAs (miRNA) address different target genes, thus have different biological functions. To identify these, the physiological expression has to be blocked. Here, we describe the use of inhibitory cholesterol-modified oligonucleotides (Antagomirs) to inhibit miRNAs selectively in primary human and murine T and B lymphocytes. Due to their lipophilic cholesterol tag Antagomirs enter primary lymphocytes efficiently and quantitatively. We show here that at concentrations of 0.125 to 1?M, Antagomirs selectively inhibit expression of their target miRNA up to 99.5% without affecting cell viability.
EVALuna2:13633

HIV-1 mRNA electroporation of PBMC: A simple and efficient method to monitor T-cell responses against autologous HIV-1 in HIV-1-infected patients - Etschel, Jennifer K.; Hueckelhoven, Angela G.; Hofmann, Christian; Zitzelsberger, Kathrin; Maurer, Katja; Bergmann, Silke; Müller-Schmucker, Sandra; Wittmann, Jürgen; Spriewald, Bernd; Dörrie, Jan; Schaft, Niels; Harrer, Thomas (Journal of Immunological Methods, 2012)
Efficient monitoring of HIV-1-specific T-cells is crucial for the development of HIV-1 vaccines and immunotherapies. Currently, mainly peptides and vaccinia vectors are used for detection of HIV-1-specific cytotoxic T-lymphocytes (CTL), however, as HIV-1 is a variable virus, it is unknown to what extent the T-cell response against the autologous virus is under- or overestimated by using antigens from heterologous viral strains. Therefore, we established a new method for immunomonitoring of CTL using electroporation of peripheral blood mononuclear cells (PBMC) with mRNA derived from autologous viral strains. From six HIV-1-infected patients virus derived mRNA was produced after PCR-based cloning of autologous gag (n = 5) and/or nef genes (n = 3) from plasma and electroporated into PBMC from patients and healthy donors. Electroporation of PBMC with mRNA resulted in efficient protein expression with good induction of γ-interferon (γ-IFN) release by specific T-cells comparable to peptide pools and better than recombinant vaccinia viruses. Three mRNA encoded autologous Gag proteins and one autologous mRNA encoded Nef protein were better recognized by autologous PBMC in comparison to heterologous mRNA encoded Gag or Nef proteins (SF2 or HXB2). However, in one case each, mRNA encoded autologous Gag or Nef, respectively, was recognized less efficiently due to the presence of CTL escape mutations. In summary, electroporation of PBMC with mRNA is a very efficient, easy and rapid method for immunomonitoring of HIV-1-specific T-cell responses against autologous viral strains. Our data demonstrate that patients' CTL responses against autologous viral strains may be under- or overestimated by using antigens from heterologous viral strains. © 2012 Elsevier B.V.
CRIS-Team Scopus Importer:2021-10-01
Keywords: CTL; HIV-1; Immunomonitoring; MRNA electroporation

miR-148a controls metabolic programming and survival of mature CD19-negative plasma cells in mice - Pracht, Katharina; Meinzinger, Julia; Schulz, Sebastian; Daum, Patrick; Corte-Real, Joana; Hauke, Manuela; Roth, Eduard; Kindermann, Dorothea; Mielenz, Dirk; Schuh, Wolfgang; Wittmann, Jürgen; Jäck, Hans-Martin (European Journal of Immunology, 2021)
Long-lived antibody-secreting plasma cells are essential to establish humoral memory against pathogens. While a regulatory transcription factor network has been established in plasma cell differentiation, the regulatory role of miRNAs remains enigmatic. We have recently identified miR-148a as the most abundant miRNA in primary mouse and human plasma cells. To determine whether this plasma cell signature miRNA controls the in vivo development of B cells into long-lived plasma cells, we established mice with genomic, conditional, and inducible deletions of miR-148a. The analysis of miR-148a-deficient mice revealed reduced serum Ig, decreased numbers of newly formed plasmablasts and reduced CD19-negative, CD93-positive long-lived plasma cells. Transcriptome and metabolic analysis revealed an impaired glucose uptake, a reduced oxidative phosphorylation-based energy metabolism, and an altered abundance of homing receptors CXCR3 (increase) and CXCR4 (reduction) in miR-148a-deficient plasma cells. These findings support the role of miR-148a as a positive regulator of the maintenance of long-lived plasma cells.
CRIS-Team Scopus Importer:2021-02-05
Keywords: CXC receptors; Glut-1; miR-148a; Oxidative phosphorylation; Plasma cells

miR-148a is upregulated by Twist1 and T-bet and promotes Th1-cell survival by regulating the proapoptotic gene Bim - Haftmann, Claudia; Stittrich, Anna-Barbara; Zimmermann, Jakob; Fang, Zhuo; Hradilkova, Kristyna; Bardua, Markus; Westendorf, Kerstin; Heinz, Gitta A.; Riedel, Rene; Siede, Julia; Lehmann, Katrin; Weinberger, Esther E.; et al. (European Journal of Immunology, 2015)
Repeatedly activated T helper 1 (Th1) cells present during chronic inflammation can efficiently adapt to the inflammatory milieu, for example, by expressing the transcription factor Twist1, which limits the immunopathology caused by Th1 cells. Here, we show that in repeatedly activated murine Th1 cells, Twist1 and T-bet induce expression of microRNA-148a (miR-148a). miR-148a regulates expression of the proapoptotic gene Bim, resulting in a decreased Bim/Bcl2 ratio. Inhibition of miR-148a by antagomirs in repeatedly activated Th1 cells increases the expression of Bim, leading to enhanced apoptosis. Knockdown of Bim expression by siRNA in miR-148a antagomir-treated cells restores viability of the Th1 cells, demonstrating that miR-148a controls survival by regulating Bim expression. Thus, Twist1 and T-bet not only control the differentiation and function of Th1 cells, but also their persistence in chronic inflammation.
EVALuna2:13629

miR-148a promotes plasma cell differentiation and targets the germinal center transcription factors Mitf and Bach2 - Porstner, Martina; Winkelmann, Rebecca; Daum, Patrick; Schmid, Julia; Pracht, Katharina; Corte-Real, Joana; Schreiber, Sandra; Haftmann, Claudia; Brandl, Andreas; Mashreghi, Mir-Farzin; Gelse, Kolja; Hauke, Manuela; et al. (European Journal of Immunology, 2015)
B cells undergo affinity maturation and class switch recombination of their immunoglobulin receptors during a germinal center (GC) reaction, before they differentiate into long-lived antibody-secreting plasma cells (PCs). Transcription factors such as Bach2 and Mitf are essential during this process, as they delay premature differentiation of GC B cells by repressing Blimp-1 and IRF4, two transcription factors required for terminal PC differentiation. Therefore, Bach2 and Mitf expression must be attenuated in activated B cells to allow terminal PC differentiation, but the precise mechanism remains enigmatic. Here, we provide evidence that miR-148a, a small noncoding microRNA, fosters PC differentiation and survival. Next-generation sequencing revealed that miR-148a is the most abundant microRNA in primary human and murine PCs, and its expression is upregulated in activated murine B cells and coincides with Blimp-1 synthesis. miR-148a targets Bach2, Mitf and proapoptotic factors such as PTEN and Bim. When prematurely expressed, miR-148a promotes the differentiation and survival of plasmablasts and reduces frequencies of IgG1(+) cells in primary B-cell cultures. In summary, we propose that miR-148a is a new player in the regulatory network controlling terminal PC differentiation and could, therefore, be a therapeutic target for interfering with PC differentiation and survival.
EVALuna2:13632

Modeling Lymphocytes - Wittmann, Jürgen (Systems Medicine, 2020)
Our immune system is continuously attacked by billions of invaders or is exposed to foreign substances. Only joint forces of various cell types, tissues and organs help to protect the body successfully against attacks from these outsiders. Endogenous threats like continuously arising, nascent transformed cells in the body also need to be recognized and eliminated. Sometimes, responses of the immune system also go awry, as in allergy, autoimmune diseases or in primary or acquired immunodeficiency disorders, leaving people more susceptible to infections due to a not properly or a not at all working immune system. The immune system is however able to cope with these manifold threats using a complex array of cellular and molecular processes. Modeling approaches have already helped achieving greater understanding of biological processes by both generating models that formalize biological ideas and by extracting information from experiments that might not be obvious or intuitive from the biological approach. Predictions and hypotheses arising from application of the models can then be tested experimentally, leading to a continuous iteration of refining the model and testing the novel predictions. To appreciate the multifaceted possibilities for modeling approaches in lymphocyte development, I first give a primer on immunology by introducing key players of the immune system and how these are generated, activated and regulated. Subsequently, I shortly discuss some cases where modeling has already helped experimental immunologists in understanding their data and offering new experimentally testable hypotheses to deepen our understanding of processes during an immune reaction.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Adaptive immunity; Affinity maturation; B cell development; B cells; B-cell receptor; CD4; CD8; Germinal center reaction; Innate immunity; Lymphocyte modeling; T cell activation; T cell development; T-cell receptor

NaV1.7 and pain: contribution of peripheral nerves - Hoffmann, Tal; Sharon, Ohad; Wittmann, Jürgen; Carr, Richard W.; Vyshnevska, Alina; De Col, Roberto; Nassar, Mohammed A.; Reeh, Peter; Weidner, Christian (Pain, 2018)
The sodium channel NaV1.7 contributes to action potential (AP) generation and propagation. Loss-of-function mutations in patients lead to congenital indifference to pain, though it remains unclear where on the way from sensory terminals to central nervous system the signalling is disrupted. We confirm that conditional deletion of NaV1.7 in advillin-expressing sensory neurons leads to impaired heat and mechanical nociception in behavioural tests. With single-fiber recordings from isolated skin, we found (1) a significantly lower prevalence of heat responsiveness to normally mechanosensitive C-fibers, although (2) the rare heat responses seemed quite vigorous, and (3) heat-induced calcitonin gene-related peptide release was normal. In biophysical respects, although electrical excitability, rheobase, and chronaxy were normal, (4) axonal conduction velocity was 20% slower than in congenic wild-type mice (5) and when challenged with double pulses (<100 milliseconds interval), the second AP showed more pronounced latency increase (6). On prolonged electrical stimulation at 2 Hz, (7) activity-dependent slowing of nerve fiber conduction was markedly less, and (8) was less likely to result in conduction failure of the mutant single fibers. Finally, recording of compound APs from the whole saphenous nerve confirmed slower conduction and less activity-dependent slowing as well as the functional absence of a large subpopulation of C-fibers (9) in conditional NaV1.7 knockouts. In conclusion, the clear deficits in somatic primary afferent functions shown in our study may be complemented by previously reported synaptic dysfunction and opioidergic inhibition, together accounting for the complete insensitivity to pain in the human mutants lacking NaV1.7.
EVALuna2:35771

Network- and systems-based re-engineering of dendritic cells with non-coding RNAs for cancer immunotherapy - Lai, Xin; Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Gerer, Kerstin F.; Jaitly, Tanushree; Uebe, Steffen; Lischer, Christopher; Ekici, Arif Bülent; Wittmann, Jürgen; Jäck, Hans-Martin; Schaft, Niels; et al. (Theranostics, 2021)
Dendritic cells (DCs) are professional antigen-presenting cells that induce and regulate adaptive immunity by presenting antigens to T cells. Due to their coordinative role in adaptive immune responses, DCs have been used as cell-based therapeutic vaccination against cancer. The capacity of DCs to induce a therapeutic immune response can be enhanced by re-wiring of cellular signalling pathways with microRNAs (miRNAs). Methods: Since the activation and maturation of DCs is controlled by an interconnected signalling network, we deploy an approach that combines RNA sequencing data and systems biology methods to delineate miRNA-based strategies that enhance DC-elicited immune responses. Results: Through RNA sequencing of IKKβ-matured DCs that are currently being tested in a clinical trial on therapeutic anti-cancer vaccination, we identified 44 differentially expressed miRNAs. According to a network analysis, most of these miRNAs regulate targets that are linked to immune pathways, such as cytokine and interleukin signalling. We employed a network topology-oriented scoring model to rank the miRNAs, analysed their impact on immunogenic potency of DCs, and identified dozens of promising miRNA candidates, with miR-15a and miR-16 as the top ones. The results of our analysis are presented in a database that constitutes a tool to identify DC-relevant miRNA-gene interactions with therapeutic potential (www.synmirapy.net/dc-optimization). Conclusions: Our approach enables the systematic analysis and identification of functional miRNA-gene interactions that can be experimentally tested for improving DC immunogenic potenc
CRIS-Team WoS Importer:2020-12-11
Keywords: dendritic cell; therapeutic vaccination in cancer; systems biology; network biology; microRNAs: bioinformatics

Selective targeting of pro-inflammatory Th1 cells by microRNA-148a-specific antagomirs in vivo - Maschmeyer, Patrick; Petkau, Georg; Siracusa, Francesco; Zimmermann, Jakob; Zuegel, Franziska; Kuehl, Anja Andrea; Lehmann, Katrin; Schimmelpfennig, Sarah; Weber, Melanie; Haftmann, Claudia; Riedel, Rene; Bardua, Markus; et al. (Journal of Autoimmunity, 2018)
In T lymphocytes, expression of miR-148a is induced by T-bet and Twist1, and is specific for pro-inflammatory Th1 cells. In these cells, miR-148a inhibits the expression of the pro-apoptotic protein Bim and promotes their survival. Here we use sequence-specific cholesterol-modified oligonucleotides against miR-148a (antagomir-148a) for the selective elimination of pro-inflammatory Th1 cells in vivo. In the murine model of transfer colitis, antagomir-148a treatment reduced the number of pro-inflammatory Th1 cells in the colon of colitic mice by 50% and inhibited miR-148a expression by 71% in the remaining Th1 cells. Expression of Bim protein in colonic Th1 cells was increased. Antagomir-148a-mediated reduction of Th1 cells resulted in a significant amelioration of colitis. The effect of antagomir-148a was selective for chronic inflammation. Antigen-specific memory Th cells that were generated by an acute immune reaction to nitrophenylacetyl-coupled chicken gamma globulin (NP-CGG) were not affected by treatment with antagomir-148a, both during the effector and the memory phase. In addition, antibody titers to NP-CGG were not altered. Thus, antagomir-148a might qualify as an effective drug to selectively deplete pro-inflammatory Th1 cells of chronic inflammation without affecting the protective immunological memory.
EVALuna2:36072

The microprocessor component, DGCR8, is essential for early B-cell development in mice - Brandl, Andreas; Daum, Patrick; Brenner, Sven; Schulz, Sebastian; Yap, Desmond Yat Hin; Boesl, Michael R.; Wittmann, Jürgen; Schuh, Wolfgang; Jäck, Hans-Martin (European Journal of Immunology, 2016)
microRNAs (miRNAs) are important posttranscriptional regulators during hematopoietic lineage commitment and lymphocyte development. Mature miRNAs are processed from primary miRNA transcripts in two steps by the microprocessor complex, consisting of Drosha and its partner DiGeorge Critical Region 8 (DGCR8), and the RNAse III enzyme, Dicer. Conditional ablations of Drosha and Dicer have established the importance of both RNAses in B- and T-cell development. Here, we show that a cre-mediated B-cell specific deletion of DGCR8 in mice results in a nearly complete maturation block at the transition from the pro-B to the pre-B cell stage, and a failure to upregulate Ig ? heavy chain expression in pro-B cells. Furthermore, we found that the death of freshly isolated DGCR8-deficient pro-B cells could be partially prevented by enforced Bcl2 expression. We conclude from these findings that the microprocessor component DGCR8 is essential for survival and differentiation of early B-cell progenitors.
EVALuna2:13647

The microRNA processing subunit DGCR8 is required for immune response and germinal center formation - Daum, Patrick; Meinzinger, Julia; Pracht, Katharina; Corte-Real, Joana; Wittmann, Jürgen; Jäck, Hans-Martin (2017)
EVALuna2:13656

Towards the generation of B-cell receptor retrogenic mice - Freitag, Jenny; Heink, Sylvia; Roth, Edith; Wittmann, Jürgen; Jäck, Hans-Martin; Kamradt, Thomas (PLoS ONE, 2014)
Transgenic expression of B- and T-cell receptors (BCRs and TCRs, respectively) has been a standard tool to study lymphocyte development and function in vivo. The generation of transgenic mice is time-consuming and, therefore, a faster method to study the biology of defined lymphocyte receptors in vivo would be highly welcome. Using 2A peptide-linked multicistronic retroviral vectors to transduce stem cells, TCRs can be expressed rapidly in mice of any background. We aimed at adopting this retrogenic technology to the in vivo expression of BCRs. Using a well characterised BCR specific for hen egg lysozyme (HEL), we achieved surface expression of the retrogenically encoded BCR in a Rag-deficient pro B-cell line in vitro. In vivo, retrogenic BCRs were detectable only intracellularly but not on the surface of B cells from wild type or Rag2-deficient mice. This data, together with the fact that no BCR retrogenic mouse model has been published in the 7 years since the method was originally published for TCRs, strongly suggests that achieving BCR-expression in vivo with retrogenic technology is highly challenging if not impossible.
EVALuna2:13620